Young Word Learners' Interpretations of Words and Symbolic Gestures Within the Context of Ambiguous Reference. Issue 1 (7th September 2012) - Suanda, Sumarga H.; Namy, Laura L.
<x xml:space="preserve">Abstract</x> Early in development, many word‐learning phenomena generalize to symbolic gestures. The current study explored whether children avoid lexical overlap in the gestural modality, as they do in the verbal modality, within the context of ambiguous reference. Eighteen‐month‐olds' interpretations of words and symbolic gestures in a symbol‐disambiguation task (Experiment 1) and a symbol‐learning task (Experiment 2) were investigated. In Experiment 1 (N = 32), children avoided verbal lexical overlap, mapping novel words to unnamed objects; children failed to display this pattern with symbolic gestures. In Experiment 2 (N = 32), 18‐month‐olds mapped both novel words and novel symbolic gestures onto their referents. Implications of these findings for the specialized nature of word learning and the development of lexical overlap avoidance are discussed.